Kynurenine System and Multiple Sclerosis, Pathomechanism and Drug Targets with An Emphasis on Laquinimod - Majlath, Zsofia; Annus, Adam; Vecsei, Laszlo (Current Drug Targets, 2018)
Multiple sclerosis is a common chronic, disabling autoimmune neurological disease affecting mainly young adults. In its pathomechanism, neurodegenerative and acute inflammatory characteristics are both involved. Disease-modifying therapies aim to reduce relapse-rate and slow down the deterioration in neurological functions. The currently available therapies fail to exert neuroprotective effects and most of them are associated with potentially toxic side-effects, therefore, ongoing research aims to develop novel drug candidates to cover these therapeutic gaps. The kynurenine pathway has been implicated in both the physiological processes of the central nervous system and in the pathomechanism of several neurological disorders as well. Alterations of the kynurenine pathway metabolites have been detected in multiple sclerosis and a number of potential therapeutic targets related to this metabolic route have been already identified. Laquinimod is a quinoline carboxamide showing structural similarities with kynurenic acid, which proved to have beneficial effects on reduction of brain atrophy and disability progression. The kynurenine pathway is therefore a promising target for the development of future drugs for the treatment of autoimmune diseases such as multiple sclerosis.
Keywords: laquinimod